Asymptotic optimality conditions for linear semi-infinite programming. (1st February 2016) - Liu, Y.; Goberna, M.A.
Abstract : In this paper, the classical KKT, complementarity and Lagrangian saddle-point conditions are generalized to obtain equivalent conditions characterizing the optimality of a feasible solution to a general linear semi-infinite programming problem without constraint qualifications. The method of this paper differs from the usual convex analysis methods and its main idea is rooted in some fundamental properties of linear programming.